EFEKTIVITAS TERAPI LATIHAN TERHADAP PENURUNAN DEPRESI PADA PASIEN STROKE - Wahyu Wijanarko; Mhd Ikhsan Nasution; Dewi Agustina (Excellent Midwifery Journal, 2020)
Exercise therapy is a systematic, planned physical exercise in posture or body training that aims to restore decreased body function, prevent or increase physical activity in order to carry out daily functional activities. Depression is a condition of feeling sad that has a negative impact on a person's thoughts, actions, feelings and mental health, in stroke sufferers this often occurs because of the inability to carry out functional activities. The purpose of this study was to determine the effectiveness of exercise therapy in reducing depression in stroke patients. The population used was all stroke patients who came to the Physiotherapy clinic at Siti Hajar Hospital Medan. Respondents used were stroke patients with depressive disorders as many as 24 respondents with purposive sampling technique, quasi-experimental design with the form of one group pre-test-post test. The results of the test analysis with the Paired T test obtained a correlation value of 0.915 which means that it has a strong and positive relationship between before exercise therapy and after it is given. The result of t count with a value of 7,218 and exceed the value of t table which means significant. At the p value of the Paired T test, the results were 0.000 (<0.05) with 95% confidence, which means that there is an effectiveness difference between before and after the treatment is given.